Methods for the algorithms for calculation of tunable coaxial bandpass microwave filters - Parfilov, A. A. (Technology and design in electronic equipment, 2012)
The article describes the features of the models and algorithms used for calculation of the characteristics of mechanically tunable coaxial bandpass microwave filters, on the basis of which a calculation computer program can be written. The ways are proposed to resolve ambiguities that arise in the course of development of the analytical algorithm for calculating coaxial tunable bandpass filters.